Determination of Some Heavy Metal Concentrations of Sage Tea with FAAS - Fevzi Kilicel; Hacer Sibel Karapinar; Ayşe Uğuz (International Journal of Secondary Metabolite)
Herbal teas are blends based on the plant's roots, root hairs, branch shoots, aromatic parts of leaves, flowers, shells, fruits, or seeds that are prepared by drying aromatic parts in the boiling water. Although the plant teas are known with many benefits in terms of health, they are an important threat for people’s life if they are exposed to some contamination due to the misuse or overuse or uncontrolled production. The living environment of the plants is polluted with many harmful substances which arise from the various sources. The factors such as the development of industry and increasing traffic, pesticides, industrial and household waste increase the heavy metal pollution. In this study, the sage teas were collected from the different localities (markets, market place, herbalist) within the province, Karaman (Turkey). The samples were taken in the sufficient quantities and analyzed by the appropriate drying, milling and dissolution processes. The samples were prepared as 2 parallels for each sample and were solved by the wet burning method. The concentrations of the examined elements were determined by Flame Atomic Absorption Spectrometry. According to the results, the amounts of Co, Ni, Cu, Zn, Cd, Mn, Mg, Fe and Ca were determined in all of the samples. Cr was not designated in the samples. Co and Cd exceeded the limits which are accepted in Europe and in Turkey. It should be noted that these foods can easily be contaminated due to the factors such as the physical and chemical structure of the soil, agricultural activities, storage and packaging conditions.